Analisis Karya Desain Gambar yang Dihasilkan ChatGPT Meniru Gaya Ghibli Studio: Perspektif Undang-Undang Hak Cipta dan Etika Bisnis Islam - Maha Bintang; Wahyu Dwi Agung Priyo Susilo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study analyzes image design works generated by ChatGPT's visual capabilities, specifically in mimicking the artistic style of Studio Ghibli, from the perspective of copyright law and Islamic business ethics. The primary focus of this research is to evaluate whether the use of a distinctive visual style by artificial intelligence constitutes a copyright infringement, and to assess its ethical implications within the framework of Islamic business principles such as justice, honesty, and the prohibition of harm to others. This research employs a qualitative approach, normative and with descriptive analysis of selected AI-generated artworks, compared against intellectual property theories and Islamic muamalah principles. The findings indicate a legal ambiguity regarding the protection of visual styles under copyright law, as well as ethical dilemmas related to the exploitation of artistic works without proper permission or appreciation for the original creators. The study recommends the development of clearer regulations and ethical guidelines concerning AI usage in the creative industry to ensure compliance with justice and integrity as upheld in Islamic business ethics.